Model uncertainty in ECB : application of Bayesian model averaging with the extended list of economic indicators - Margaryan, Hasmik (2022)
Uncertainty is one of the most important aspects of monetary policies. Recent economic and political events showed that uncertainty is omnipresent and that policymakers should take it into account in their decision-making process. Uncertainty can take many forms from data uncertainty to model uncertainty, which are very important to consider in monetary policies. Recent global financial crisis also highlighted that conventional monetary policies have their limits and that unconventional monetary policies should be considered. It also showed that the monetary policy models failed to take into account essential economic and financial variables and, therefore, don’t capture the whole economic development. The aim of this thesis is to analyze the monetary policy models with the extended list of economic and financial variables. It has the aim to extend the application of Bayesian Model Averaging in ECB monetary policies. The thesis comes to the conclusion that the inclusion of wide set of macroeconomic variables will lead to more effective monetary policy decisions.